E-commerce: A Study on the Online Purchasing behavior of Generation Y in Malaysia - Tan, Su Han (2009)
Purpose: This study is conducted aimed to discover the factors which will directly influence the Generation Y’s online purchasing behavior in Malaysia, as well as exploring their purchasing criteria while making online purchase.